Enhanced simultaneous nitrogen and phosphorus removal via a step-feed anoxic/oxic process coupled with side-stream enhanced biological phosphorus removal - Ruoyu Wu; Dongqi Wang; Mengbo Huang; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Wengui Gu; Lu Qin; Yuan Guo; Xiaopeng Qiu; Yishan Lin; Da Kang; et al. (Journal of Environmental Chemical Engineering, 2026)

Intermittent stirring-mediated solids retention time–hydraulic retention time decoupling enhances side-stream enhanced biological phosphorus removal performance and microbial selection - Yanzhe Gong; Dongqi Wang; Wengui Gu; Ruoyu Wu; Guangxiang Duan; Jiayu Bi; Xiaopeng Qiu; Yuan Guo; Yishan Lin; Hongfang Sun; Xi Wen; Chenxin Tang; et al. (Journal of Environmental Chemical Engineering, 2026)

Dynamics and community succession of surface-associated biofilms on microplastics in a full-scale wastewater treatment plant - Yu Li; Dongqi Wang; Yanzhe Gong; Shengwei Zhang; Mengbo Huang; Wenqi Liang; Ruoyu Wu; Xiaosheng Jing; Yishan Lin (Journal of Water Process Engineering, 2026)

Effects of alkaline pretreatment on side-stream enhanced biological phosphorus removal and recovery process - Ruoyu Wu; Dongqi Wang; Yufan Wu; Lu Qin; Xiaonian Feng; Yi Xiao; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Zhiqiang Xu; Yuan Guo; Jiake Li; et al. (Journal of Water Process Engineering, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

Impact of acid mine drainage on water quality in receiving watersheds and associated potential adverse effects - Hao Wang; Guodong Chai; Heyun Yang; Kailong Li; Kai Chen; Yueyao Xue; Jiake Li; Zhe Wang; Chunbo Jiang; Huaien Li; Fan Yang; Yishan Lin; et al. (Process Safety and Environmental Protection, 2025)

Gem-like starch granules engineered with different crystalline starches - Ruikang Lin; Xufeng Zang; Wenjie Zhang; Ying Tian; Yishan Fang (Food Chemistry, 2025)

Impact of mining activities on sediment resistance genes and microbial diversity along a receiving watershed - Guodong Chai; Yishan Lin; Kailong Li; Kai Chen; Wenhui Xu; Hui Wang; Jiake Li; Xiaosheng Jing; Haiyu Meng; Zhe Wang; Yuan Guo; Chunbo Jiang; et al. (Journal of Environmental Chemical Engineering, 2025)

Long-term impact of Hurricane Maria on point-of-use drinking water quality in Puerto Rico and associated potential adverse health effects - Yishan Lin; Guangyu Li; Maria Sevillano Rivera; Tao Jiang; Irmarie Cotto; Corey M.G. Carpenter; Stephanie L. Rich; Roger W. Giese; Damian E. Helbling; Ingrid Y. Padilla; Zaira Rosario-Pabón; Akram N. Alshawabkeh; et al. (Water Research, 2024)

Developments in molecular docking technologies for application of polysaccharide-based materials: A review - Ruikang Lin; Jihui Zhang; Ruoxuan Xu; Chao Yuan; Li Guo; Pengfei Liu; Yishan Fang; Bo Cui (Critical Reviews in Food Science and Nutrition, 2024)

Cloning, Characterization and Functional Analysis of Caspase 8-like Gene in Apoptosis of Crassostrea hongkongensis Response to Hyper-Salinity Stress - Jinji Lin; Ziqi Yu; Yang Leng; Jiexiong Zhu; Feifei Yu; Yishan Lu; Jiayu Chen; Wenhao He; Yixin Zhang; Yaoshen Wen (Fishes, 2024)
Caspase-8, a member of the caspase family, is an initiating caspase and plays a crucial role in apoptosis. In this study, the full-length cDNA of caspase8-like (CASP8-like) was isolated from Crassostrea hongkongensis (C. hongkongensis) by RACE-PCR. ChCASP8-like contained a 1599-bp open reading frame (ORF) encoding 533 amino acids with two conserved death effector domains (DEDs) and a cysteine aspartase cysteine structural domain (CASc). Amino acid sequence comparison showed that ChCASP8-like shared the highest identity (85.4%) with CASP8-like of C. angulata. The tissue expression profile showed that ChCASP8-like was constitutively expressed in gills, hepatopancreas, mantle, adductor muscle, hemocytes and gonads, and was significantly upregulated in hemocytes, hepatopancreas and gills under hyper-salinity stress. The apoptosis-related genes, including ATR, CHK1, BCL-XL, CASP8-like, CASP9 and CASP3, were significantly activated by hyper-salinity stress, but were remarkably inhibited by ChCASP8-like silencing. The caspase 8 activity was increased by 1.7-fold after hyper-salinity stress, and was inhibited by 9.4% by ChCASP8-like silencing. Moreover, ChCASP8-like silencing clearly alleviated the apoptosis resulting from hyper-salinity stress. These results collectively demonstrated that ChCASP8-like played a crucial role in inducing apoptosis against hyper-salinity stress.

Self-growing micro/nano hexagonal cyclodextrins based on dual enzyme synergism and low-temperature induction - Ruikang Lin; Xufeng Zang; Chao Yuan; Bing Yu; Pengfei Liu; Yishan Fang; Bo Cui (Chemical Engineering Journal, 2024)

AMPKα is active in autophagy of endothelial cells in arsenic-induced vascular endothelial dysfunction by regulating mTORC1/p70S6K/ULK1 - Ziqi Xu; Qiaoling Liu; Jinyu Li; Jingqiu Wang; Zhihan Yang; Juan Wang; Lin Gao; Jin Cheng; Jing He; Yishan Dong; Xiangnan Guo; Jing Cui; et al. (Chemico-Biological Interactions, 2024)

Dual cross-linked starch hydrogel for eugenol encapsulation and the formation of hydrogen bonds on textural hydrogel - Ruikang Lin; Ruoxuan Xu; Huiyi Chen; Bo Liu; Chao Yuan; Li Guo; Bo Cui; Yishan Fang (Carbohydrate Polymers, 2023)

A novel water disinfection method via cuprous ion generation in a copper ferrite/sulfite system and associated mechanism - Lu Qin; Dongqi Wang; Cong Liu; Guodong Chai; Mingliang Fang; Jiake Li; Hui Wang; Zhe Wang; Haiyu Meng; Xing Zheng; Mengbo Huang; Yi Xiao; et al. (Journal of Water Process Engineering, 2023)

Creb2 involved in innate immunity by activating PpMitf-mediated melanogenesis in Pteria penguin - Feifei Yu; Zexin Du; Zhiming Zhong; Xiangyong Yu; Jiayu Chen; Yishan Lu; Jinji Lin (Fish & Shellfish Immunology, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Effects of organic substrates on sulfate-reducing microcosms treating acid mine drainage: Performance dynamics and microbial community comparison - Guodong Chai; Dongqi Wang; Yitong Zhang; Hui Wang; Jiake Li; Xiaosheng Jing; Haiyu Meng; Zhe Wang; Yuan Guo; Chunbo Jiang; Huaien Li; Yishan Lin (Journal of Environmental Management, 2023)

TLR4 involved in immune response against Vibrio Parahaemolyticus by MyD88-dependent pathway in Crassostrea hongkongensis - Feifei Yu; Jiayu Chen; Jinji Lin; Zhiming Zhong; Yishan Lu; Xiangrong Zeng; Xiaoya Lei (Fish & Shellfish Immunology, 2023)

Highly selective adsorption of Hg (II) from aqueous solution by three-dimensional porous N-doped starch-based carbon - Chao Geng; Ruikang Lin; Peilin Yang; Pengfei Liu; Li Guo; Bo Cui; Yishan Fang (Environmental Science and Pollution Research, 2023)

Effects of different carbon sources and carbon–nitrogen ratios on the survival, growth, intestinal biochemical parameters, and water quality of seahorse juveniles cultured under zero-water exchange conditions - Tingting Lin; Yishan Cai; Xin Liu; Siping Li; Dong Zhang; Lianjun Xia (Aquaculture International, 2022)

Heavy Rainfall Events Following the Dry Season Elevate Metal Contamination in Mining-Impacted Rivers: A Case Study of Wenyu River, Qinling, China - Dong Chen; Yi-ping Chen; Yishan Lin (Archives of Environmental Contamination and Toxicology, 2021)

Clinical characteristics of 24 asymptomatic infections with COVID-19 screened among close contacts in Nanjing, China - Zhiliang Hu; Ci Song; Chuanjun Xu; Guangfu Jin; Yaling Chen; Xin Xu; Hongxia Ma; Wei Chen; Yuan Lin; Yishan Zheng; Jianming Wang; Zhibin Hu; et al. (Science China Life Sciences, 2020)